Trapezium Fracture Associated with Thumb Carpometacarpal Joint Dislocation: A Report of Three Cases and Literature Review - Sho Kohyama; Toshikazu Tanaka; Akira Ikumi; Yasukazu Totoki; Kosuke Okuno; Naoyuki Ochiai (Case Reports in Orthopedics)
Isolated trapezium fracture in combination with thumb carpometacarpal (CMC) joint dislocation is extremely rare, and no treatment consensus exists. Herein, we report 3 successfully treated cases of isolated trapezium fracture with thumb CMC joint dislocation. While good short-term results have been reported in the literature, the possibility of substantial ligament injuries that can lead to future instability of the thumb CMC joint must be noted. In order to obtain an excellent long-term clinical result, we propose the consideration of the anatomical repair of the CMC joint in terms of both bony and ligamentous structures in cases where instability remains after fracture fixation.